1996
DOI: 10.1046/j.1365-3156.1996.d01-47.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV and India: looking into the abyss

Abstract: Summary Serosurveillance of high risk groups started in India in October 1985. The first positive case were detected in 1986. As of mid‐1994, official figures stood at 15 000 HIV positive cases and 559 cases of AIDS. This is most certainly an underestimate because of under reporting. Among high risk groups, prevalence has risen rapidly. Between 1986 and 1994, prevalence has risen from 1.6 to 40.0% in sex workers, 1.4 to 40% in STD clinics and 0 to 70% in i.v. drug abusers in various studies. The penetration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…1,2 This global epidemiological picture is being replicated in India; as the epidemic accelerated in the early 1990s, gender distribution estimates for 1994 indicated a male to female ratio of 5:1, with female cases mostly among sex workers. 3 By the end of the decade, the epidemic had crossed over to the general population, and gender ratios had reduced to a 3:1 ratio with current estimates at 1.7:1. [4][5][6][7] Women currently represent an estimated 40% of the 5.1 million people aged 15-49 living with HIV/AIDS in India.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This global epidemiological picture is being replicated in India; as the epidemic accelerated in the early 1990s, gender distribution estimates for 1994 indicated a male to female ratio of 5:1, with female cases mostly among sex workers. 3 By the end of the decade, the epidemic had crossed over to the general population, and gender ratios had reduced to a 3:1 ratio with current estimates at 1.7:1. [4][5][6][7] Women currently represent an estimated 40% of the 5.1 million people aged 15-49 living with HIV/AIDS in India.…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of HIV/STD infected individuals in India are men; estimates in 1994 indicated a male to female ratio of 5:1, with female cases being mainly sex workers (Pais, 1996). More recent estimates indicate a 2.5:1 ratio (UNAIDS, 2002).…”
Section: "Seizing the Day"mentioning
confidence: 99%
“…51 This was con rmed in the early 1990s by studies of 608 multi-transfused thalassaemic children that showed a seropositiv e rate of just under 9%. 52 Until then, the dominant view was that HIV/AIDS was a foreign disease, with the result that compulsory blood tests for foreigner students was introduce and persons testing positive were deported. Tests for Indian citizens, however, were not generally required.…”
Section: Hiv/aids Seropositivity and The Origins Of Indian Bloodmentioning
confidence: 99%